One-pot synthesis of an emulsion-templated hydrogel-microsphere composite with tunable properties. (October 2018) - Lai, Wing-Fu; Rogach, Andrey L.; Wong, Wing-Tak
Abstract: The development of composite hydrogels is enjoying ever-increasing research interests and applications due to the high flexibility of these materials in composition and properties. This study develops an emulsion-templated hydrogel-microsphere composite with tunable properties using a one-pot synthetic approach. The composite consists of poly(trimethylolpropane ethoxylate triacrylate) microspheres crosslinked by a hydrogel, which is formed by a starch-based bifunctional emulsion stabilizer. Composites with a higher compositional ratio of the hydrogel have been found to have lower erosion susceptibility and swelling capacity. As an illustration of the unique practical potential of its amphiphilic character and tunable swelling properties, as well as its large surface area for adsorption, the composite has been loaded with model compounds with various degrees of hydrophilicity, and has been shown to be useful for applications such as drug loading and pollutant removal. The composite is a novel material displaying application potential that warrants further development.